Modal Sosial dan Humas Kultural: Menakar Strategi Pesantren dalam Mempertahankan Eksistensi dan Animo Masyarakat - Rowiyanto; Laili Syarifah (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
The institutional sustainability and enrollment rates of traditional Islamic boarding schools (pesantren) in Central Java have experienced post-pandemic anomalies due to intensifying educational competition and shifting urban demographic preferences. This study aims to analyze the management of public relations (PR) in enhancing parent enrollment interest (animo) at Pondok Pesantren Nurul Ali Sempu, Secang, Magelang. Utilizing a qualitative, descriptive-naturalistic approach, data were gathered through non-participant observation, semi-structured interviews, and documentation. Informants were selected via purposive sampling, including the head of the pesantren, 44 board members, 7 parents, and 6 alumni. Data were analyzed using the Miles and Huberman interactive model, encompassing data collection, data reduction, data display, and conclusion drawing. The findings reveal that the implementation of PR at Pondok Pesantren Nurul Ali shifts away from modern transaction-based public relations towards a cultural and socio-religious approach that strategically capitalizes on social capital (bonding and bridging social capital). This is manifested through inclusive and participatory annual PR programming, the mobilization of alumni and thariqoh networks as grassroots brand ambassadors, and a dual-track communication mix that blends the charismatic interpersonal diplomacy of the Kyai (head priest) with transparent digital publication platforms. Furthermore, the institutionalization of a continuous, two-way feedback loop with the parent council serves as a strategic mechanism to evaluate and refine educational services. This study concludes that the synthesis between adaptive public relations management and deep-rooted social capital creates a high-trust educational ecosystem, which ultimately acts as a robust catalyst to maintain institutional resilience, enhance accountability, and significantly boost parent enrollment interest in the competitive education market.